Reading Psalm 22 in Mark 15 through a postcolonial lens: A pedagogical approach for South African theological education - Hombana, Mphumezi (Verbum et ecclesia, 2025)
This article explores Mark’s use of Psalm 22:1 in the crucifixion narrative (Mk 15:34) as a postcolonial theological act and pedagogical resource within the South African context. It argues that Mark’s appropriation of the Psalm is not a mere citation but a dynamic reinterpretation that reconfigures the traditional understanding of divine abandonment, reframing it as a site of eschatological hope, resistance and theological transformation. Drawing on the Jewish liturgical practice of invoking the whole Psalm through its opening verse, the article contends that Mark’s readers would have perceived Jesus’ cry not solely as despair, but as a deliberate evocation of the Psalm’s trajectory from lament to restoration. This re-reading disrupts conventional atonement paradigms by locating divine presence within the experience of forsakenness, thereby offering theological solidarity with communities that continue to suffer under postcolonial conditions. The article also demonstrates how this reading of Mark 15:34 functions pedagogically in South African theological education. Teaching methods that integrate lament traditions, postcolonial hermeneutics and indigenous African grief practices open interpretive space for students to confront themes of abandonment, injustice and resilience. While students initially resist the shift from doctrinal to contextual readings, the engagement with postcolonial biblical scholars facilitates a critical consciousness that reimagines the cross as a narrative of resistance and identity reconstruction. The article concludes that Mark’s intertextual engagement with Psalm 22 invites a pedagogy of hope and theological agency, enabling marginalised communities to articulate their suffering and faith within a framework of redemptive lament. Intradisciplinary and/or interdisciplinary implications: This article contributes to postcolonial biblical scholarship by offering a reconfiguration of Mark 15:34 as a theological and pedagogical resource that centres lament as a form of resistance. It advances a postcolonial hermeneutic that situates divine presence within the experience of abandonment, resonating with the historical traumas of marginalised South African communities. Additionally, it proposes a praxis-oriented pedagogy that bridges academic exegesis with indigenous forms of grief and theological agency.